Abscisic Acid Promotes Jasmonic Acid Accumulation and Plays a Key Role in Citrus Canker Development - Long, Qin; Xie, Yu; He, Yongrui; Li, Qiang; Zou, Xiuping; Chen, Shanchun (Frontiers in Plant Science, 2019)
Antagonism between jasmonic acid (JA) and salicylic acid (SA) plays pivotal roles in the fine-tuning of plant immunity against pathogen infection. In this study, we compared the phytohormonal responses to Xanthomonas citri subsp. citri (Xcc) between the citrus canker-susceptible (S) cultivar Wanjincheng orange (Citrus sinensis Osbeck) and -resistant (R) cultivar Jindan (Fortunella crassifolia Swingle). Upon Xcc infection, SA and JA were strongly induced in Jindan (R) and Wanjincheng orange (S), respectively, and JA appeared to contribute to citrus disease susceptibility by antagonizing SA-mediated effective defenses. A homologous gene encoding the allene oxide synthase (AOS) 1-2 enzyme, which catalyzes the first committed step in JA biosynthesis, was specifically upregulated in Wanjincheng orange (S) but not in Jindan (R). A promoter sequence analysis showed that abscisic acid (ABA)-responsive elements are enriched in the AOS1-2 of Wanjincheng orange (S) but not in Jindan (R). Accordingly, ABA treatments could induce AOS1-2 expression and JA accumulation, leading to enhanced citrus disease susceptibility in Wanjincheng orange (S), while the synthesis inhibitor sodium tungstate had the opposite effects. Moreover, ABA was specifically induced by Xcc infection in Wanjincheng orange (S) but not in Jindan (R). Thus, Xcc appeared to hijack host ABA biosynthesis to promote JA accumulation, which in turn suppressed effectual SA-mediated defenses to favor disease development in citrus. Our findings provide new insights into the molecular mechanisms underlying the differential citrus-canker resistance in citrus cultivars, and a new strategy for the biotechnological improvement of citrus canker resistance was discussed.